Three-Dimensional Elastic-Plastic Crack Tip Stress Fields - Mohd Nor Halimuddin, Normalyana (Universiti Sains Malaysia, 2022)
The constraint impact is the most important factor in structural integrity evaluations aspects on crack tip fracture mechanics to accurately anticipate the stresses condition of material under the influence of crack. This thesis investigates a stress field changes along the thickness and around the angle of the crack-tip. Through modification of the analytical formulas proposed using HRR-J-∆